Muscle activation differences between stable push-ups and push-ups with a unilateral v-shaped suspension system at different heights - Calatayud,Joaquin (2014)
This study was designed to analyze upper extremity and core muscle activation performing push-ups under different stability conditions and body positions. Trained university male students (n= 29) performed 3 push-ups each under stable conditions and using suspension device (AirFit Trainer ProTM) with their hands at 2 different heights (i.e., 10 and 65 cm). Push-up speed was controlled using a metronome and the testing order was randomized. The average amplitudes of the electromyographic root mean square of the Triceps Brachii, Upper Trapezius, Anterior Deltoid, Clavicular Pectoralis, Rectus Abdominis, Rectus Femoris, Lumbar Erector Spinae and Gluteus Maximus were recorded and normalized to the maximum voluntary isometric contraction. A repeated-measures analysis of variance with a Bonferroni post hoc test was used to analyze data. Suspended push-ups provided greater activity than the stable condition, except for the Anterior Deltoid and Clavicular Pectoralis. Therefore, suspended push-ups are especially advantageous if the goal of the exercise is targeting the TRICEP, TRAPS and/or core training. Overall, performing push-ups at 65 cm from the floor decreases exercise intensity and muscle activity in comparison with the 10 cm position.